PERANCANGAN UI/UX ADHA KOST MENGGUNAKAN METODE DESIGN THINKING - Fathan Fakhrana Auafar; Putri Yuli Utami, Rizki Surtiyan Surya (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The development of the boarding house business in the city of Pontianak is increasing, but this does not necessarily mean that potential consumers can easily find boarding houses. Information obtained from various media created by boarding house owners, such as uploading photos and videos on social media platforms such as Facebook, Instagram and others, is considered to be less effective. The design thinking method is a collaborative method that collects many ideas to obtain a solution. Design Thinking has comprehensive thinking to get a solution with 5 method stages, namely empathize, define, ideate, prototype and test, with this method you can solve existing problems. To connect boarding house owners and potential consumers, one way is to create a website-based application related to the availability of boarding rooms to make it easier for boarding house seekers to find boarding houses and boarding house owners to market boarding houses. To make the website usable well requires a website design that can be easily accessed or used either as a boarding house seeker or boarding house owner. Designing using the Design Thinking method makes it easier to create UI / UX for Adha Kost. Apart from that, designing the design using the Design Thinking method makes the design look more attractive and the items used are more complete in accordance with the user's needs